2023
DOI: 10.1111/jre.13109
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin inhibits osteogenic differentiation of human periodontal ligament stem cells

Abstract: Background and Objective: Periodontal ligament stem cells (PDLSCs) are derived from the periodontal ligament and have the characteristics of pluripotent differentiation, including osteogenesis, and are one of the important seed cells in oral tissue engineering. Thyrotropin (TSH) has been shown to regulate bone metabolism independently of thyroid hormone, including the fate of osteoblasts and osteoclasts, but whether it affects osteogenic differentiation of PDLSCs is unknown. Materials and Methods:PDLSCs were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…Given the fact that OSA patients generally have worse progress in diabetic ulcer treatment, the protective effect of upregulated miRNA-31 on wound healing may work only in some cases or be a part of a specific subset responsible for the repair (Maltese et al, 2018). The same miRNA was upregulated in the retina (Kovacs et al, 2011) and periodontal ligament (Zhen et al, 2017) of diabetic rats, and in endothelial progenitor cells obtained from T2DM patients (Lian et al, 2018). (Freude et al, 2012).…”
Section: Diabetes Mellitusmentioning
confidence: 97%
“…Given the fact that OSA patients generally have worse progress in diabetic ulcer treatment, the protective effect of upregulated miRNA-31 on wound healing may work only in some cases or be a part of a specific subset responsible for the repair (Maltese et al, 2018). The same miRNA was upregulated in the retina (Kovacs et al, 2011) and periodontal ligament (Zhen et al, 2017) of diabetic rats, and in endothelial progenitor cells obtained from T2DM patients (Lian et al, 2018). (Freude et al, 2012).…”
Section: Diabetes Mellitusmentioning
confidence: 97%
“…A scoping review also found a positive relationship between hypothyroidism and periodontitis 6 . In turn, there is evidence that thyroid dysfunction was significantly linked to the development of periodontitis, independent of various risk factors for periodontitis 7–9 . However, the evidence for causal relation concerning periodontitis and thyroid function is limited, with only few observational studies available.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of specific surface antigens, including CD44, CD73, CD90, and CD105, helps characterize MSCs, while lacking hematopoietic and endothelial markers [30]. Indeed, MSCs are defined by their plastic adherence, capacity of self-renovation, and the potential for differentiation in vitro into different types of cells, like osteoblasts, adipocytes, and chondroblasts, under specific stimuli [31,32]. Many intraoral and dental sources of MSCs are available, for example, dental pulp, periodontal ligament, bone marrow from alveolar bone, dental follicle, gingival connective tissue, or apical papilla [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%